Proceedings of the 2nd International Conference on Education, Humanities, Health and Agriculture, ICEHHA 2022, 21-22 October 20 2023
DOI: 10.4108/eai.21-10-2022.2329666
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomathematical Studies in the Scopus Database Between 2010-2022: A Bibliometric Review

Abstract: Today, ethnomathematics studies have become a global trend for decades. However, there is no comprehensive understanding of the state of studies on ethnomathematical topics to date. For this reason, this study seeks to fill these limitations by conducting a bibliometric study of 198 studies on the Scopus database between 2010 and 2022. This research addresses two issues: (i) an overview of the growth trajectory of studies related to ethnomathematics; and (ii) mapping to identify the most important gaps and top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…The research results show that the number of publications between 2010-2019 is very significant. This is in line with the results of bibliometric analysis from previous studies, which showed an increasing trend until 2019 [1], [3], [21]- [23]. Furthermore, the downward trend from 2019 to 2021 was mediated by the impact of COVID-19, as seen from the results of previous research in 2019 [21].…”
Section: Fig 3 Mapping Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…The research results show that the number of publications between 2010-2019 is very significant. This is in line with the results of bibliometric analysis from previous studies, which showed an increasing trend until 2019 [1], [3], [21]- [23]. Furthermore, the downward trend from 2019 to 2021 was mediated by the impact of COVID-19, as seen from the results of previous research in 2019 [21].…”
Section: Fig 3 Mapping Analysissupporting
confidence: 91%
“…Integrating ethnomathematics as part of a didactic framework in mathematics learning has recently become a recommended option [1]- [3]. Applying ethnomathematics is an important part of getting closer to students and their inherited culture so that it can be passed on to the next generation [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini dibuktikan dengan berkembangnya penelitian ethnomatematika dari waktu ke waktu. Perkembangan tersebut mencakup eksplorasi matematika dalam suatu budaya, penerapan nilai-nilai budaya ke dalam pembelajaran matematika, pengembangan perangkat pembelajaran berbasis budaya, hingga pengembangan model pembelajaran berbasis ethnomatematika (Kharisudin & Iqbal, 2021;Tamur et al, 2023). Perkembangan ethnomatematika juga ditunjukkan dengan adanya pendekatan yang lebih mendalam dalam ethnomatematika, yang disebut ethnomodelling (Alghar & Jamaluddin, 2024;Rosa & Orey, 2017).…”
Section: A Etnomatematikaunclassified